HUBUNGAN KELENTUKAN TOGOK, DAYA LEDAK OTOT TUNGKAI, DAN KEKUATAN OTOT TUNGKAI TERHADAP SERVIS SLICE TENIS LAPANGAN - Ricko Irawan (Universitas Negeri Semarang, 2014)
The purpose from this observation is for knowing the relationship among stake flexibilty, leg power, and strength of leg towards service slice in tennis. I do survey test for data collection by testing and measuring. The observation instrument for stake flexibility uses by sit and reach, leg power uses by jump DF, strength of leg uses by back and leg dynamometer, and service slice uses by J.E. Hewwit s Tennis Achievement Test. The value from this data is all about free variable data ; stake flexibility (x1), leg power (x2), strength of leg (x3), and bound of variable which is speed service slice. This research shows us that : (1) There is a connection between stake flexibility and service slice. (2) There is a connection between leg power and service slice. (3) There is a connection between strength of leg and service slice. (4) There is a connection among stake flexibility, leg power, strength of leg, and service slice.